Searching for success: A mixed methods approach to identifying and examining positive outliers in development outcomes. (September 2019) - Peiffer, Caryn; Armytage, Rosita
Highlights: Positive outliers are valuable as they show how progress occurs against the odds. Researchers have largely relied on experts to identify positive outliers. By relying on experts, less well known positive outliers have been overlooked. A 3-stage methodology promises to uncover 'hidden' cases of developmental progress. The methodology is used to identify under recognised cases of bribery reduction. Abstract: Increasingly, development scholars and practitioners are reaching for exceptional examples of positive change to better understand how developmental progress occurs. These positive outlying cases are often referred to as 'positive exceptions', but also 'positive deviants' and 'pockets of effectiveness'. Studies in this literature promise to identify and examine positive developmental change occurring in otherwise poorly governed states. However, to identify success stories, such research largely relies on the reputations of cases, and, by doing so, overlooks cases that have not garnered a reputation for their developmental progress. This paper presents a novel three-stage methodology for identifying and examining positive outlier cases that does not rely solely on reputations. It therefore promises to uncover 'hidden' cases of developmental progress as well as those that have been recognized. The utility of the methodology is demonstrated through its use in uncovering two case studies in which surprising rates of bribery reduction occurred, though the methodology has much broader applicability. The advantage of the methodology is validated by the fact that, in both cases identified, the reductions in bribery that occurred were previously unrecognized.